Study of Mobile Sms Security Issues and Techniques: Exploring SMS security issues and future research directions (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The short message service (SMS) isone of the highly used and well-tried mobile services with global availabilitywithin all GSM networks. The existing SMS is limited to the transmission ofsecure plain text between different mobile phone subscribers. SMS does not haveany built-in procedure to authenticate the text and offer security for the texttransmitted as data, because most of the applications for mobile devices aredesigned and developed without taking security into consideration. This paperdetails an overview of the current SMS security aspects and concerns during theSMS transmission. It also chronologically presents the existing mechanisms usedto protect the SMS with the goal to provide useful advices for furtherresearch. In addition, the security and efficiency of these mechanisms areanalysed, considering the limitation on the mobile devices and the securityrequirements. Finally it suggests the SMS security future direction forgenerating extra research topics.